Determinación de niveles de ruido rodado en la Avenida Antonio José de Sucre y su posible Influencia en el Campus Universitario - Montesdeoca Poma, Pamela Nicole (2019)
The purpose of this research is to determine the levels of noise rolled on Antonio José de Sucre Avenue, from the Begonias intersection to the Jaime Roldós Aguilera intersection due to the incidence of existing vehicle flow in the area, for this purpose vehicles can be selected from categories Lightweight of type Sedan, Suv, Pik Up and the category of Heavy Bus vehicle, to which the Close Proximity Method (CPX method) was applied to determine the noise levels generated by the pavement rim interaction with 90 ° angle variations 45 ° and 130 °. Likewise, as a basis in the study, prediction models of vehicular traffic noise levels were used in this case were: RLS-90 from Germany, and the NMPB-Routes-96 model from France, these methods will be used to analyze, compare and apply the results with the data thrown by the measurement made in selected points in the study area. The specified values of vehicular traffic noise served as a reference to determine the level of total rolling noise. The results obtained show us values that exceed 85 dB, these values are projected on strategic noise maps, the use of Geographic Information Systems (GIS) software. The study is concluded by determining that the noise pressure values of the rolling noise affected exceed the permissible limits, with the lowest incidence being the Sedan category and the highest incidence category Suv and Pik Up.